Asymmetric Tunable Photonic Bandgaps in Self‐Organized 3D Nanostructure of Polymer‐Stabilized Blue Phase I Modulated by Voltage Polarity. (23rd October 2017) - Wang, Meng; Zou, Cheng; Sun, Jian; Zhang, Lanying; Wang, Ling; Xiao, Jiumei; Li, Fasheng; Song, Ping; Yang, Huai
Abstract: Electrically responsive photonic crystals represent one of the most promising intelligent materials for technological applications in optoelectronics. In this research, a polymer‐stabilized blue phase (PSBP) I film with the self‐organized 3D nanostructure is fabricated, and an electrically tunable photonic bandgap (PBG) is achieved. Interestingly, the large‐scale shift of the PBG covering the entire visible spectrum is found to be asymmetric and can be modulated by the polarity and magnitude of bias voltage. Moreover, to demonstrate the usability in optical devices, blue phase lasers are developed by doping the PSBP material with fluorescent dyes. And mirrorless lasing emission with electrically tunable wavelength is observed. This self‐assembled soft material is prospective to produce large‐scale electrically responsive photonic crystals in facile fabrication process and has enormous potential applications in intelligent optoelectronic devices, such as 3D tunable lasers, reflective full‐color displays, or photonic integrated circuits. Abstract : Self‐organized 3D nanostructure of polymer‐stabilized blue phase I with electric‐induced reversible tuning of photonic bandgap covering the visible spectrum is developed. The shifting of the photonic bandgaps can be facilely modulated by the polarity and magnitude of applied direct current field, and the practical application for electrically tunable lasers is demonstrated.